2007
DOI: 10.1109/iembs.2007.4352834
|View full text |Cite
|
Sign up to set email alerts
|

NIRS Measurement of Hemodynamic Evoked Responses in the Primary Sensorimotor Cortex

Abstract: To investigate the relationship between neuronal activity and hemodynamics, we carried out a near-infrared spectroscopy (NIRS) study to measure the regional changes of hemoglobin concentration associated with cortical activation in the human sensorimotor cortex (SMI) to both voluntary and nonvoluntary tasks. We measured the hemodynamic evoked responses to voluntary finger movement and nonvoluntary electrical stimulation applied on the fingers (thumb and ring finger, respectively). Measurements were performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…HHb concentration increases or decreases after stimulus onset. Similar discrepancies have been described further as partial volume effect (Boas et al, 2001, Strangman et al, 2002b, Huppert et al, 2006, Xu et al, 2007. Partial volume effect is the effect wherein insufficient image resolution leads to a mixing of different tissue types.…”
Section: Partial Volume Effectsupporting
confidence: 56%
“…HHb concentration increases or decreases after stimulus onset. Similar discrepancies have been described further as partial volume effect (Boas et al, 2001, Strangman et al, 2002b, Huppert et al, 2006, Xu et al, 2007. Partial volume effect is the effect wherein insufficient image resolution leads to a mixing of different tissue types.…”
Section: Partial Volume Effectsupporting
confidence: 56%
“…In addition, several studies have reported that NMES has a direct effect on the cortical activation [16-19]. On the other hand, some studies have reported changes of cortical activation with functional recovery of the hemiparetic hand after long-term intensive treatment by NEMS [20,21]. However, little is known about the short-term effect on the changes of cortical activation during motor performance after application of NMES.…”
Section: Introductionmentioning
confidence: 99%
“…Several functional neuroimaging techniques, such as functional MRI, magnetoencephalography, Positron Emission Tomography, and functional near infrared spectroscopy (fNIRS) are available for use in studies of brain activation induced by NMES [18,20-23]. Among these techniques, fNIRS, a new emerging distinguished optical instrument, based on the intrinsic optical absorption of blood, enables noninvasive measurement of regional relative hemodynamic responses associated with cortical activation [24-28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation